Study of local manifestations of snake bite and its surgical implications, at a rural hospital in India - Srivastava, Shirish; Patel, Vishwa; Rangwala, Varin (International Journal of Research in Medical Sciences, 2022)
Background: Manifestations of snakebite have local and systemic implications. While systemic manifestations can be life-threatening, local complications like cellulitis, necrosis, and compartment syndrome secondary to snakebite can threaten limb survival. This study undertakes the recognition of local complications and its outcome. Methods: A retrospective observational study was conducted at our tertiary center in India. 219 snake bitten patients presenting in between January 2013 to December 2020, were studied. Surgical interventions whenever required for managing local surgical complications were recorded and analyzed. Results: Of the 219 patients, 118 (53.88%) of the patients were bitten by venomous snakes requiring systemic therapy and 101 (46.12%) were non-venomous. Of the 118 patients with venomous snakebite, 78 (35.62%) had signs and symptoms. 83.11% reported to the hospital within 6 hours of the bite, while 45.66% within 2 hours. There were 169 (77.17%) patients who had local signs of inflammation, ischemic changes in 28 (12.79%), compartment syndrome in 15 (6.88%). 167 (76.26%) patients were treated conservatively while 52 (23.74%) had to undergo surgical interventions. Those undergoing surgical interventions had longer hospital stays (mean=8.09615) as compared to those treated conservatively (mean=4.82635) (p value=< 0.001). In patients with no local inflammation, only 1 (0.46%) required surgical intervention as compared to 51 (23.29%) (p value=< 0.001) patients with local inflammation requiring surgical intervention. Conclusions: Along with systemic medical treatment, local manifestations of most snakebites can be well managed with suitable surgical intervention. Surgical complications of snakebite are not infrequent leading to interventions. Such patients usually have a longer hospital stay.